PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPESTUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVA SDN 12 PEKANBARU - Dewi Erliana; Erlisnawati '; zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study was motivated by the large number of students whohave not completed 22 students while the students who completed ie 12 students with an average of 64.65. Formulation of the problem in this study is whether the learning model type Cooperative Learning Student Teams Achievement Divisioans (STAD) can improve learning outcomes Mathematics IVA grade students of SD Negeri 12 Pekanbaru ?This research aims to improve learning outcomes throug Cooperative Learning Model Student Teams Achievement Divisioans (STAD) in Class IVA SD Negeri 12 Pekanbaru. Methods This study uses a Class Action Research conducted in two ( 2 ) cycles with 4 ( four ) stages: planning, action, observation, and reflection. As a basis to make re-planning in the next cycle. From this research result UH I learned from the first cycle an average of 78.68 has increased 21.70%. While on siklusn II increased to 82.65 increased from baseline by 27.84%. Results of the data analysis activities of teachers at the first meeting of the first cycle with a 50.33 percentage (category enough). The second meeting of the first cycle with a percentage of 70.83% (both categories). The first meeting of the second cycle with a percentage of 87.5% (category very good) and the second meeting of the second cycle with the percentage of 95.83% (very good category ). While the activities of the first cycle students first meeting with persentase54,17% ( category enough). The second meeting of the first cycle with a percentage of 66.67% (both categories). At the first meeting of the second cycle with the percentage of 83.33% ( category very good ), and the second meeting of the second cycle with percentages of 91, 66% ( very good category ). At the first meeting of the second cycle with the percentage of 83.33% (category very good), and the second meeting of the second cycle with percentages of 91, 66% (very good category). From the results of this study concluded that the application of cooperative learning teaching model type Divisioans Student Teams Achievement (STAD) can improved learning outcomes Mathematics IVA grade students of SD Negeri 12 Pekanbaru.Key words : Cooperative type Divisioans Student Teams Achievement (STAD Mathematics learning outcomes